Computer-aided assessment in statistics: the CAMPUS project - Neville Hunt (Association for Learning Technology, 1998)
The relentless drive for 'efficiency' in higher education, and the consequent increase in workloads, has given university teachers a compelling incentive to investigate alternative forms of assessment. Some forms of assessment with a clear educational value can no longer be entertained because of the burden placed on the teacher. An added concern is plagiarism, which anecdotal evidence would suggest is on the increase yet which is difficult to detect in large modules with more than one assessor. While computer-aided assessment (CAA) has an enthusiastic following, it is not clear to many teachers that it either reduces workloads or reduces the risk of cheating. In an ideal world, most teachers would prefer to give individual attention and personal feedback to each student when marking their work. In this sense CAA must be seen as second best and will therefore be used only if it is seen to offer significant benefits in terms of reduced workloads or increased validity.